The Prevalence of Kounis Syndrome and COVID-19 Vaccination-A Comprehensive Review - Ekambaram, Bhavya; Suresh, Swetha; John, Jerphene Franklin; Kamaraj, Nithish Kumar Jothi (International Journal of Pharmaceutical Investigation, 2025)
Background Kounis Syndrome (KS) or allergic myocardial infarction is a rare, complicated Coronary Artery syndrome (CAD) which develops concurrently with an allergy or hypersensitivity reaction. It is also termed as Allergic Angina or Allergic Myocardial Infarction. The Coronary Artery Disease (CAD) is caused by Atherosclerotic plaque accumulation, a condition in which the coronary arteries that deliver blood, oxygen and nutrients to the heart muscle constrict or become clogged due to this, blood supply to the heart is reduced which can cause angina (chest discomfort) and dyspnea. The syndrome has well-defined clinical and diagnostic significance highlighting the involvement of inflammatory mediators in cardiovascular pathology. Objectives To provide an overview on the pathophysiology, classification, triggers, clinical presentation, diagnosis, treatment and prognosis of Kounis Syndrome. Materials and Methods A review of current literature on the mechanisms, clinical features and management strategies for KS, focusing specifically on the need for simultaneity in the recognition of allergic and coronary symptoms. Results Kounis Syndrome (KS) is a rare condition where Acute Coronary Syndromes (ACS) is linked to allergic reactions. This happens because substances like histamine and tryptase are released. There are 3 types: vasospasm without Coronary Artery Disease (CAD), plaque disruption with existing CAD and hypersensitivity causing stent thrombosis. Triggers can be drugs, foods, insect bites, or environmental allergens. Symptoms include chest pain, ECG changes and allergic signs like rash and anaphylaxis. Diagnosis involves looking at the patient's history, identifying the allergen and checking for signs of ischemia and allergic reaction. Treatment includes antihistamines, corticosteroids, epinephrine (used carefully) and standard ACS treatments. The outcome depends on how much the coronary arteries are affected and the severity of the reaction. Conclusion Kounis Syndrome is an allergy and cardiovascular pathology which indicates their connection. More public awareness through the medical community and the provision of better reporting are surely crucial in order to have more information of its epidemiology and adequate patient care. More studies should be carried out to elucidate the mechanisms and to prescribe effective treatments in the case of Kounis Syndrome.
Keywords: Acute coronary syndromes; COVID-19 vaccination; Hypersensitivity reaction; Kounis Syndrome